The Effect of the Numbered Heads Together Cooperative Model on Students' Speaking Skills in Indonesian Language Learning - Umi Rohimah; Eddy Noviana; Dede Permana (Raja Zulkarnain Education Foundation, 2026)
The Numbered Heads Together (NHT) cooperative learning model is a type of cooperative learning designed to influence student interaction patterns and as an alternative to traditional classroom structures that provide opportunities for students to share ideas and consider the right answers and also encourage students to increase their spirit of cooperation. This study aims to describe the results of the pre-test and post-test of speaking skills and the effect of the NHT model on speaking skills in Indonesian language learning. This study was conducted in grade IV of SD Mit Fathrizk Laman Wak Atan, Pekanbaru which took place in the 2025/2026 academic year. This study used a quantitative approach with a pre-experimental method through a one-shot case study design. The research subjects were 25 students. Pre-test and post-test data for speaking skills were collected using an oral test in the form of a retelling task of learning materials assessed based on six indicators of speaking skills, namely pronunciation, fluency, vocabulary, grammar, content coherence, and self-confidence. Data were analyzed using descriptive statistics. The results of the study showed that the pre-test speaking skills were in the moderate category, while the students' speaking skills after implementing the NHT learning model were in the high category. The NHT model had a positive effect on speaking skills in Indonesian language learning in fourth grade.